Trypanosoma vivax in Dairy Cattle - Lopes, Sabrina Thabla Pereira; Prado, Bruno da Silva; Martins, Gustavo Henrique Chaves; Beserra, Hiran Esmeraldo Albuquerque; Filho, Marcos Antônio Celestino de Souza; Evangelista, Luanna Soares de Melo; Cardoso, Janaina de Fátima Saraiva; Mineiro, Ana Lys Bezerra Barradas; de Souza, José Adalmir Torres (Acta Scientiae Veterinariae, 2018)
Background: Trypanosoma vivax is a protozoan that causes reproductive disorders and decreased production in domestic and wild ungulate animals. The bovine are the main hosts of the disease and the transmission occurs by the bite of hematophagous insects, mainly tabanids. Several diagnostic techniques can be used to detect the parasite, both in parasitological form and by serological kits. In Brazil, the disease has been reported in bovines, goats and sheep of some states, with high morbidity and mortality and due to the scarcity of results on the epidemiology of the disease, this work had the objective to report the presence of T. vivax in a female bovine of a dairy herd in Parnaíba county, Piauí. Case: The animal naturally infected by Trypanosoma vivax, was a three-year-old cow from a dairy farm in the Parnaíba county, located in the north of Piauí state. The farm had a herd whith 62.20% of young Girolando breed cows and the breeding system used was semi-confinement, with two mechanical milking per day. At the time of a Veterinarian’s technical visit to the property, it was observed the occurrence of abortions, mastitis, estrus repetitions and cows with hematuria, leading to the suspicion of the bovine leptospirosis occurrence. Blood samples were collected from 78 cows from the herd for hematological, biochemical and serological tests, and 72 (92.30%) were reactive to some Leptospira serovars. All the exams were carried out at the Federal University of Piauí (UFPI). In the group of animals negative for leptospirosis, a female was diagnosed positive for bovine trypanosomiasis, confirming the result in the blood smear. This animal had no clinical signs characteristic of the disease at the time of the evaluation. Discussion: Blood trypomastigote forms of Trypanosoma vivax were visualized on several slides of the animal smear and all the morphological structures of the parasite found were clearly seen under microscopyas described in the literature. The hematological alterations observed were normochromic normocytic anemia, thrombocytopenia, leukocytosis due to lymphocytosis, monocytosis and eosinophilia. The anemia and leukocytosis clinical condition found in the specific animal is commonly found in bovines naturally infected by trypanosomiasis in the chronic phase of the disease. The results of the serum biochemistry revealed decreased blood glucose and increased renal and hepatic parameters, as well as the inversion of the albumin-globulin ratio. Similar laboratory results were also described previously. The animal had a good body score, a good diet and showed no clinical signs of the disease. A good nutrition may have controlled the T. vivax parasitaemia, avoiding the characterization of the clinical condition. This fact can be attributed to the differences in pathogenicity of the parasite and/or susceptibility of a particular host. In the area of the farm where the cattle were housed the presence of several tabanids was noticed and the increase of these insects in the environment is considered a risk factor, predisposing, even, the occurrence of new outbreaks. The epidemiological situation of the disease in Brazil is described, for the most part, by reports of outbreaks or specific events, revealing the lack of more consistent studies. With this result it is known that trypanosomiasis exists in the dairy herd of the state of Piauí, being important to carry out new work to diagnose the epidemiological situation of the disease within the productive context of our region. Keywords: bovine, dairy herd, trypanosomiasis.